The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15288/jsad.2015.76.957
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the Relationship Between Anxiety Sensitivity and Alcohol Use

Abstract: ABSTRACT. Objective:The misuse of alcohol is related to numerous detrimental health effects. Research has determined anxiety sensitivity (AS) to be a risk factor for problematic alcohol use. To date, no studies have investigated this relationship using a bifactor model of AS. This study used a bifactor model to determine the effects of the general AS factor and the cognitive, physical, and social concerns subfactors on alcohol-related outcomes. Method: The sample consisted of 329 participants selected from a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…The ASI-3 is composed of a total score and three lower-order subscales: AS cognitive concerns, AS physical concerns, and AS social concerns. The ASI-3 has exhibited strong psychometric properties, including internal consistency, factor stability, and divergent validity (Chavarria et al, 2015 ; Farris et al, 2015 ; Taylor et al, 2007). In the current study, the ASI-3 total, cognitive, physical, and social scores demonstrated good internal reliability ( α ’s = .93, .90, .89, and .83, respectively).…”
Section: Study 1 – Methodsmentioning
confidence: 99%
“…The ASI-3 is composed of a total score and three lower-order subscales: AS cognitive concerns, AS physical concerns, and AS social concerns. The ASI-3 has exhibited strong psychometric properties, including internal consistency, factor stability, and divergent validity (Chavarria et al, 2015 ; Farris et al, 2015 ; Taylor et al, 2007). In the current study, the ASI-3 total, cognitive, physical, and social scores demonstrated good internal reliability ( α ’s = .93, .90, .89, and .83, respectively).…”
Section: Study 1 – Methodsmentioning
confidence: 99%
“…We tested whether AS is a risk factor for, or complication of, alcohol misuse by conducting a comprehensive meta-analysis. While cross-sectional research has found conflicting evidence of AS's association with quantity of alcohol use (Stewart et al, 1995(Stewart et al, , 2001, research does suggest AS is related to increased frequency of alcohol consumption (Stewart et al, 2001), frequency of binge drinking (Stewart et al, 1995(Stewart et al, , 2001, and alcohol-related problems (Chavarria et al, 2015). Given these findings, we expected to find similar results in prospective research on AS.…”
Section: Objectives and Hypothesesmentioning
confidence: 99%
“…Although preliminary work following the Taylor et al (2007) development of the ASI-3 confirmed the initial three-factor structure (Kemper et al, 2012; Wheaton et al, 2012), an emerging body of evidence now supports a bi-factor structure for the ASI-3 (Allan et al, 2015; Chavarria et al, 2015; Ebesutani et al, 2014; Osman et al, 2010; Rifkin et al, 2015). A bi-factor model separates a general factor (e.g., anxiety sensitivity) that is orthogonal with a set of subfactors (e.g., physical concerns, cognitive concerns, and social concerns) and can determine, based upon the degree to which individual items load onto the general factor and the specific subfactors, whether a scale is better represented as multidimensional or unidimensional (Reise et al, 2010).…”
Section: Introductionmentioning
confidence: 96%